Community-based fish culture in seasonal floodplains and irrigation systems - Sheriff, N.; Joffre, Olivier M.; Hong, M.C.; Barman, B.K.; Haque, A.B.M.M.; Rahman, F.; Zhu, J.; Brakel, Martin L. van; Valmonte-Santos, Rowena; Werthmann, C.; Kodio, A.; Nguyen, H. van; et al. (CGIAR Challenge Program on Water and Food, 2010)
The overall objective of the project was to enhance fish production from seasonally flooding areas and irrigation systems using a collective approach to fish culture. The project sought to examine the institutions necessary to support community-approaches to fish culture in a range of social, cultural and economic conditions, in Bangladesh, Cambodia, China, Vietnam and Mali. Technical designs for fish culture were also tested, building on successes achieved in earlier trials in Bangladesh, with an emphasis on adapting the model to develop locally appropriate culture systems. The project showed that the model is able to generate important benefits for communities in Bangladesh, China and Mali, and may have the potential to so in other countries. However, it was found that introducing fish culture into complex and dynamic institutional contexts, whereby open access waters lie over private property required a range of social, environmental and economic conditions to be in place for the adoption and continuance of the fish culture model.